A complicated case of granulomatosis with polyangiitis - Guchev, Filip; Bojadjioska, Maja; Vidinikj, Sonja; Sandevska, Emilija; Petrova, Sanja; Antova, Dubravka; Vasilevska, Ana; Vejseli, Ron (Macedonian Academy of Sciences and Arts/Walter de Gruyter GmbH, 2025)
Granulomatosis with polyangiitis, formerly known as Wegener's granulomatosis, is a condition often presenting with granulomatous vasculitis of both the upper and lower respiratory tracts together with glomerulonephritis. Here we present a case of a 17-year-old female patient, who presented with symptoms of pansinusitis with other symptoms gradually following. She was treated with cyclophosphamide which was later switched to rituximab and is now in remission.
Keywords: cyclophosphamide; granulomatosis polyangiitis; pansinusitis; rituximab; vasculitis